2016
DOI: 10.1177/0042098015613003
|View full text |Cite
|
Sign up to set email alerts
|

A(nother) geography of fear: Burmese labour migrants in George Town, Malaysia

Abstract: While scholarship around urban fear has brought forward important insights around the relationship between fear, mobility and social exclusion, questions relating to legal exclusion have largely been left outside the scope of inquiry. In cities around the world there are, however, a growing number of people who are not only de facto excluded from rights to/within the city (based on their gender, class, age etc.) -but de jure excluded based on their non-citizen or 'illegal' status in the host country. Drawing u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
0
18
0
2
Order By: Relevance
“…The stories told by the residents in this Jelutong apartment capture the way that migrants' relationship to urban space is mediated through their immigration status (Franck 2016). Whereas the disciplinary effects of 'illegality' and 'deportability' in migrants' everyday lives (and perhaps especially in the labour market) have been discussed elsewhere (de Genova 2002), this study highlights how legal exclusions also produce particular/distinct everyday geographies (Franck 2016;Holgersson 2011;Willen 2007).…”
Section: Navigating the City As A Borderscapementioning
confidence: 75%
See 1 more Smart Citation
“…The stories told by the residents in this Jelutong apartment capture the way that migrants' relationship to urban space is mediated through their immigration status (Franck 2016). Whereas the disciplinary effects of 'illegality' and 'deportability' in migrants' everyday lives (and perhaps especially in the labour market) have been discussed elsewhere (de Genova 2002), this study highlights how legal exclusions also produce particular/distinct everyday geographies (Franck 2016;Holgersson 2011;Willen 2007).…”
Section: Navigating the City As A Borderscapementioning
confidence: 75%
“…The stories told by the residents in this Jelutong apartment capture the way that migrants' relationship to urban space is mediated through their immigration status (Franck 2016). Whereas the disciplinary effects of 'illegality' and 'deportability' in migrants' everyday lives (and perhaps especially in the labour market) have been discussed elsewhere (de Genova 2002), this study highlights how legal exclusions also produce particular/distinct everyday geographies (Franck 2016;Holgersson 2011;Willen 2007). Navigating urban space much like a borderscape, the migrants in George Town described how the reoccurring and constantly displaced police controls mediated their ability to takes possession of urban space, and thus preconditioned many aspects of their everyday lives (Franck 2016).…”
Section: Navigating the City As A Borderscapementioning
confidence: 99%
“…The rules for foreign workers in Malaysia are narrowly defined and are designed to give workers relatively little room for manoeuvre while also trying to ensure that their stay is temporary (Nah 2012;Franck 2016). The Malaysian government specifies which industries an individual may work in depending on their nationality and gender (Immigration Department of Malaysia 2018).…”
Section: Research Context and Methodologymentioning
confidence: 99%
“…Similar allegations have been made related to Malaysia's labour agreement with Bangladesh, with high levels of bribery and the channelling of lucrative contracts to well-connected individuals (The Star 2018a; Zsombor 2019). Within Malaysia, police officers frequently perform document checks, but these can be evaded through the paying of bribes (Franck 2016).…”
Section: Research Context and Methodologymentioning
confidence: 99%
“…Barriers to health care constitute just one facet of the health challenges facing 'disposable' migrants. Difficulties with access to justice make migrants with irregular status easy targets for exploitation, extortion, forced labour and trafficking (Azis 2014;Franck 2016). In a study of more than one thousand asylum seekers and refugees from Burma (Myanmar), the non-governmental organisation Health Equity Initiatives (2011) found that around one-third had experienced forced labour.…”
Section: Rendering Migrants 'Disposable'mentioning
confidence: 99%